Pendekatan Makna Al-Qital dan Batasan Etiknya Dalam Al-Qur’an - Muhammad Suaib Tahir (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2018)
Violence and terrorism that occurred in various countries both in the West and in the East, especially Indonesia is widely claimed as a form of resistance to the West. Unfortunately this action is mostly done by a number of Muslims and understand the act as a manifestation of jihad. These acts of violence often appear sporadically that casualties are not only the target of action, but sometimes civilians and Muslims, not only in political, economic and thought but also in the fundamental aspect of the crisis of self-understanding. This can be seen from the concept of jihad sometimes understood as the concept of war (qital) solely against the disbelievers. Whereas the meaning of war is only one of the special meanings of jihad that is used in a limited way beyond the universal meanings that are universal. From the search for qital and elaboration verses of relevant studies it is known that war in the Qur’an is a form of defensive effort to defend and defend against aggression, eliminate slander and freedom of religion and to free the oppressed people of the persecution. Despite limited availability, war is a test of faith as jihad in general which must always be in the corridor fi sabilillah.